Correlation between magnetic resonance imaging and arthroscopic findings of meniscus injuries of the knee joint - Dhan Bahadur Karki; Pratap Babu Bhandari; Bipan Shrestha; Kishor Man Shrestha; Shreshal Shrestha; Subash Pandey; Anil Kumar Chaudhary; Sanjeeb Rijal (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTION MRI (Magnetic Resonance Imaging) findings of meniscal injuries may not always match the arthroscopic finding. Thus, the aim of this study was to evaluate the correlation between MRI findings and arthroscopic findings of meniscal injuries of the knee joint. MATERIAL AND METHODS This was cross-sectional study conducted in Universal college of medical science teaching hospital in which the MRI findings of the patients undergoing arthroscopic knee surgery over a period of 6 months are studied and compared with arthroscopic findings for meniscus injury. Sensitivity, Specificity, Positive predictive value (PPV), Negative predictive value (NPV) and accuracy of MRI findings in the diagnosis of meniscus injuries by comparing with arthroscopic findings are calculated. Chi square test will be used to find the association between different selected variables, p value < 0.05 will be considered significant. RESULTS The sensitivity and specificity of both meniscuses were 88.2% and 91.3% with accuracy 90.00%. PPV 88.2% and NPV 91.3%, Chi square=0.125, p=0.72. The sensitivity, specificity, accuracy, PPV and NPV were 85.7%, 88.5%, 87.5%, 80.0% and 92.0% respectively for lateral meniscus whereas for medial meniscus were 90%, 95%, 92.5% 94.7% and 90.5% respectively CONCLUSION MRI is a highly useful, non-invasive diagnostic tool for the evaluation of meniscal injuries. Its diagnostic accuracy is consistently higher for medial meniscus tears compared to lateral tears. This study found no evidence of a statistically significant association between MRI findings and arthroscopy findings.